Transcriptomic analysis of oxidative stress mechanisms induced by acute nanoplastic exposure in Sepia esculenta larvae - Liu, Xiumei; Yang, Jianmin; Li, Zan (Frontiers in Physiology, 2023)
Nanoplastics (NPs), as a new type of pollutant with a size small than 1 μm, are ubiquitous and harmful to organisms. There has been an increasing amount of research concerning the effects of NPs on organisms over recent years, especially on aquatic animals. However, there is a limited study on the impact of NPs on mollusk cephalopods. In this research, Sepia esculenta, belonging to Cephalopoda, Coleoidea, Sepioidea, was selected to explore the effects caused by NPs exposure. The S. esculenta larvae were exposed to polystyrene NPs (PS-NPs) with diameter 50 nm (100 mg/L) for 4 h. The detection of oxidative stress biomarkers displayed an obvious increase in SOD (superoxide dismutase) activity and MDA (malondialdehyde) level. Then, RNA-Seq was performed to explore the oxidative stress response at mRNA level. The transcriptome analysis demonstrated that the expression of 2570 genes was affected by PS-NPs. Besides, the signaling pathways of ribosome, ribosome biogenesis in eukaryotes, proteasome, and MAPK were enriched. This study not only provides novel references for understanding the mechanisms of oxidative stress response induced by NPs, but also reminds us to follow with interest the influence of acute exposure to NPs.